The Effect of Accounting Information (Net Cash Flow, Return on Equity, and Company Size) on Stock Returns in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2018 Period - Shofia Asry (Kusuma Negara Business School, 2020)
One of the investment activities that can be done is by investing in securities or stocks. The stock itself is evidence of equity participation in a company. Efficient Market Hypothesis explains that stock prices reflect all available information, which means that any information that can be used to predict stock performance will be reflected in stock prices. The sample objects of the companies studied were manufacturing companies on the Indonesia Stock Exchange for 2018, where their financial reports have been published and have been audited. The stock price which is the object of the dependent variable is the price per March 31, which is the last reported price when the shares are sold on the stock exchange, where three months after the end of the fiscal year, at this time the stock price reflects all information available in the market. This price occurs after the shares are listed on the stock exchange (secondary market price), and on March 31 all audit reports have been submitted. The partial test results show that the cash flow variable does not have a significant effect on stock returns, while the ROE and size variables have a significant effect on stock returns. Simultaneous test results show column sig. 0.000 <0.05 level of significant (a). This means that simultaneously the independent variable has a significant effect on the dependent variable. This means that the null hypothesis (Ho) is rejected, while the alternative hypothesis (Ha) is accepted. The ability of the independent variable in explaining the dependent variable in this model is 37.8%, while the remaining 62.2% is caused by other variables outside this model. Based on these results, by looking at the small number of variables that have a significant effect on price movements and stock returns, it shows that the capital market in Indonesia is still not efficient. In other words, this study proves that the Grand Theory: Efficient Market Hypothesis has not been implemented in Indonesia.